Malaysia's Socio-Economic Transformation : Ideas for the Next Decade - Basu Das, Sanchita; Lee, Poh Onn (Singapore : Institute of Southeast Asian Studies, 2014)
Since 1957, Malaysia's economic development has been an account of growth, transformation, and of structural change. More than 75 per cent of its gross domestic product (GDP) comes from the manufacturing and services sectors. However, Malaysia is stuck in a middle-income trap and is facing challenges on the economic and political front. In June 2010, Prime Minister Najib Razak unveiled the 10th Malaysian Plan (2011-15) to chart the development of Malaysia from a middle- to high-income nation. This publication represents a policy-oriented stocktake and evaluation by academics, policy-makers, and business people on Malaysia's achievements, present work-in-progress endeavours, and some of the future challenges facing the nation in its pursuit to achieve a developed high-income country status.
Title from publisher's bibliographic system (viewed on 24 Nov 2015).
Keywords: Malaysia -- Economic conditions; Malaysia -- Politics and government; Malaysia -- Social policy; Malaysia -- Social conditions; Malaysia -- Economic policy